Coaching by age: An analysis of coaches` paternalistic leadership on youth athletes` organizational citizenship behavior in China - Li, J.; Li, S.; Hu, J.; Chen, R. (Frontiers in Psychology, 2021)
Based on social cognitive theory, we studied the relationship between coaches` paternalistic leadership (PL) and youth athletes` organizational citizenship behavior (OCB) and the mediation effect of athletes` trust in coaches, in China. This age-specific research was conducted among more than 2,000 Chinese youth soccer players. Overall, 758 youth soccer players, aged 13-18 years, completed a self-report questionnaire. The results showed that the three dimensions of the coaches` PL have different relationships with OCB, and the differences were due to differences in athletes` ages. Additionally, we verified the mediation role of trust. Our research conclusions are of great significance to the study of Chinese youth soccer as in-depth research can provide a deeper and more precise understanding of the relationship between PL and the OCB of Chinese youth soccer players. This study expands the literature on social cognitive theory and sheds light on the relationship between coach leadership and athlete OCB by providing extensive evidence.